2012
DOI: 10.3389/fnhum.2012.00084
|View full text |Cite
|
Sign up to set email alerts
|

A neuroanatomical examination of embodied cognition: semantic generation to action-related stimuli

Abstract: The theory of embodied cognition postulates that the brain represents semantic knowledge as a function of the interaction between the body and the environment. The goal of our research was to provide a neuroanatomical examination of embodied cognition using action-related pictures and words. We used functional magnetic resonance imaging (fMRI) to examine whether there were shared and/or unique regions of activation between an ecologically valid semantic generation task and a motor task in the parietal-frontoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…In that study, authors found activation in the pre- and post-central gyrus during action-verb generation (Peran et al, 2010). Similarly, other authors found activation for the semantic generation task in proximity of the hand or foot motor cortex (Esopenko et al, 2012). It has been argued that action-related representations are involved in tasks implying active semantic search during the generation of action verbs (Peran et al, 2010).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In that study, authors found activation in the pre- and post-central gyrus during action-verb generation (Peran et al, 2010). Similarly, other authors found activation for the semantic generation task in proximity of the hand or foot motor cortex (Esopenko et al, 2012). It has been argued that action-related representations are involved in tasks implying active semantic search during the generation of action verbs (Peran et al, 2010).…”
Section: Introductionsupporting
confidence: 54%
“…Before we address the implications of our main finding, we first discuss results concerning the anatomo-functional correlates of the action-verb generation task in healthy participants and in neurosurgical patients with lesions involving the motor system and the main differences between their activations under classical General Linear Model assumptions. The task-related network reflected language processing; the activations encompassed areas which have been shown by fMRI and PET studies to be involved in semantic processing (e.g., Tettamanti et al, 2005; Peran et al, 2010; Esopenko et al, 2012); areas reflecting language processing were the ventral occipital cortex bilaterally extending to the left anterior superior temporal gyrus and the left TPJ; areas activated in conjunction with bilateral activations of the premotor cortex were found bilaterally in the superior parietal cortex and in the left intraparietal sulcus. These findings confirm earlier reports of a general role of these areas in semantic processing (Chao and Martin, 2000; Price, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Recchia and Jones (2012); Yap et al (2012) show that words that generate more features in feature listing tasks produce faster naming, lexical decision, and semantic categorization responses, Hargreaves et al (2012a) report that those words are also better remembered in free recall. Finally, there is evidence supporting embodied frameworks of semantic memory from studies reported by Esopenko et al (2012); McNorgan (2012). Further support for the embodied framework is provided by Hansen et al (2012); Hargreaves et al (2012b); Newcombe et al (2012); Tousignant and Pexman (2012); Yap et al (2012), as all of these studies report body-object interaction effects (faster processing for words that refer to objects the human body can easily interact with) in tasks that include naming, lexical decision, and semantic categorization.…”
Section: Meaning Is Multidimensionalmentioning
confidence: 58%
“…Interestingly, M1 was activated despite verbs being presented in a third singular person perspective, M1 was found activated in contrast with previous studies in which authors doubted whether they did not found M1 activation because they used the third person perspective (Gilead et al, 2013), consistently with a TMS study showing that motor simulation occurs for verbs in the first, but not in the third person perspective (Papeo et al, 2009). Semantic generation task, in which participants were instructed to quickly describe how they would physically interact with the visually presented pictures or words referring to objects that are typically used by hand or the foot, activated somatotopically M1 (Esopenko et al, 2012). …”
Section: Mental Rotation and Action-related Word Processingmentioning
confidence: 99%